Data underpinning "Interacting climate change environmental factors effects on Fusarium langsethiae growth, expression of Tri genes and T-2/HT-2 mycotoxin production on oat-based media and in stored oats" - Verheecke-Vaessen, Carol; Magan, Naresh; Diez, Lucia; Renaud, Justin; Sumarah, Mark; Medina, Angel (Cranfield University, 2019)
The objectives of this study were to investigate the impact that interactions between key climate change (CC) related environmental factors of temperature (20, 25, 30°C), water activity (aw; 0.995, 0.98) and CO2 exposure (400, 1000 ppm) may have on (a) growth, (b) gene expression of biosynthetic toxin genes (Tri5, Tri6, Tri16), and (c) phenotypic T-2/HT-2 production by Fusarium langsethiae on oat-based agar medium and in stored oats. Fungal growth was optimum at 25°C and 0.995 aw and reduced significantly at 30°C and intermediate stress (0.98 aw, elevated CO2 (1000 ppm) exposure by approx. 4-fold. Lag phases prior to growth paralleled these results with the longest lag phase in this treatment (24 hrs). On oat-based medium, the relative Tri5 gene expression was increased in elevated CO2 conditions. The expression of both the Tri6 and Tri16 genes was reduced when compared to control (20°C, 0.995 aw, 400 ppm), especially in elevated CO2 conditions. In stored oats, the Tri5 gene expression was reduced in all conditions except at 30°C, 0.98 aw, elevated CO2 where there was a significant (5.3-fold) increase. The expression of the Tri6 was slightly over-expressed in elevated CO2 and the Tri16 gene was upregulated, especially in elevated CO2 conditions. For mycotoxin production, both on oat-based medium and in stored oats the production was higher at 25°C when compared to 30°C. In stored oats, at 0.98 aw, elevated CO2 led to higher T2/HT-2 toxin production at both 25 and 30°C with a significant increase (73-fold higher) at 30°C. In elevated CO2 conditions, Tri16 (Spearman test; 0.68; p-value=0.0019) and Tri5 gene expression (Spearman test; 0.56; p-value=0.0151) were correlated with T-2+HT-2 production. Nine T-2 and HT-2 metabolites were detected by LC-MS/MS including a new dehydro T-2 toxin and the conjugate, HT-2 toxin glucuronide (in plantae). The new dehydro T-2 toxin was the most abundant metabolites and showed correlation (R2=0.8176) with T-2 production. This is the first study to examine the impact of CC factors on growth and mycotoxin production by a strain of F. langsethiae. The influence of such scenarios on relative risk of oats contamination with these toxins in relation to the food security agenda is discussed.'
Keywords: Biosynthetic genes'; 'Carbon dioxide'; 'Mycotoxins'; 'Small grain Cereals'; 'Temperature'; 'Type A trichothecenes'; 'Mycology'